Safe Transfer Method of Verifiable Credentials Based on Self-Sovereign Identity - Lim, Seungjoo; Kim, Ki Hyung (Journal of Korean Institute of Communications and Information Sciences, 2022)
Self-Sovereign Identity(SSI) is rapidly emerging as the importance of self-sovereignty guarantee becomes increasingly important in the digital identity model. World Wide Web Consortium(W3C) is standardizing the Verifiable Credential(VC) to realize SSI. While the standards for VC focus on the authentication, the authorization is relatively not yet dealted with, only mentioning the need for the appropriate implementation of an authorization framework based on VC and a risk of infringement of self-sovereignty because there is no specification of security requirements or detailed structures. In particular, it is difficult to guarantee self-sovereignty in this case due to the lack of specifications for transmitting credentials to others in the VC standard. This paper proposes a method for safely transmitting credentials to others while protecting self-sovereignty.
Keywords: Authorization; Blockchain; Identification; Network Security; Self-Sovereign Identity